Neural Interfaces: An Injectable Neural Stimulation Electrode Made from an In‐Body Curing Polymer/Metal Composite (Adv. Healthcare Mater. 23/2019). Issue 23 (5th December 2019) - Trevathan, James K.; Baumgart, Ian W.; Nicolai, Evan N.; Gosink, Brian A.; Asp, Anders J.; Settell, Megan L.; Polaconda, Shyam R.; Malerick, Kevin D.; Brodnick, Sarah K.; Zeng, Weifeng; Knudsen, Bruce E.; McConico, Andrea L.; et al.
Abstract : The Injectrode is an in‐body curing material that forms an electrode contact with nerves to enable minimally‐invasive neuromodulation. The artwork depicts the spirit of Kip A. Ludwig's, Andrew J. Shoffstall's, and co‐workers' effort in article number 1900892 ; to bridge electrical pulses from the outside of the body to nerves on the inside. In this case, a representation of the vagus nerve.